Public understanding of malaria in pregnancy : selected Dar es Salaam audiences' reception of the health education film Chumo - Nkwera, Godfrey (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2015)
This study examines the impact of a health education film, Chumo, in Dar es Salaam on knowledge about malaria in pregnancy. Specifically, the study examines the meanings that the selected audiences make after watching the film. Drawing on the tradition of 'reception studies', the data for this study was generated through focus group discussions. These discussions were preceded by thematic analysis of the film and its script. An analysis of the audiences' responses reveals that Chumo, mostly, successfully conveyed new knowledge about malaria in pregnancy, and reinforced existing knowledge bases about the disease. The audiences were able to 'decipher' most of the preferred meanings (of the producers) with regard to the disease, particularly in relation to the transmission of the disease and its prevention in pregnant woman. For example, the analysis indicates that both women and men become more aware of the importance of attending antenatal care sessions at local clinics (hereafter ANC). An interesting finding is that men, mostly, expressed a reluctance to attend ANC with their wives because they fear having to undergo HIV/AIDS testing. Men also expressed the sentiment that attending ANC is a women's responsibility. The discussion groups also raised issues about the use of insecticide-treated nets - some people believe that using them will affect their health because of the chemicals used to treat the nets. From the reception analysis, various other meanings and themes, relating to the choice of storylines and gender stereotypes used in the story, were raised in discussion. The study attempted to assess whether the storyline was advantageous in conveying the core educational messages, or if some elements of the storyline either 'got in the way' or reinforced gender roles in ways that may or may not be helpful in terms of combatting malaria in pregnancy. The study also found that Chumo stimulated interpersonal communication, which may trigger behaviour change. It can be demonstrated, at least for the participants in these focus groups, that the film motivated positive attitudes towards behaviour change, i.e. created at least some intention to change. However, interpersonal communication and attitude to change are not, of course, actual change of behaviour: these elements only indicate the possibility of behaviour change in the future. Further study needs to be undertaken to explore whether the actual change took place and whether the change is a result of the exposure to Chumo.
Keywords: Chumo (Television program); Malaria in pregnancy -- Tanzania -- Dar es Salaam; Health education -- Tanzania -- Dar es Salaam; Communication in medicine -- Tanzania -- Dar es Salaam; Sex role -- Tanzania -- Dar es Salaam; Health behavior -- Tanzania -- Dar es Salaam; Health behavior -- Sex differences -- Tanzania -- Dar es Salaam